Bacteriuria following Foley catheterization after gynecological and obstetrical surgery - Ojha, Neebha (Nepal Journal of Obstetrics and Gynaecology, 2008)
Objective: To find out the frequency of bacteriuria associated with Foley catheterization after gynecological and Obstetric (cesarean section) surgery and to analyze the factors associated with bacteriuria. Methods: This is a retrospective study conducted in the Department of Obstetrics and Gynecology of TUTH. Hospital chart records of one of the four functional units for a period of one year (1st January 2007 to 31st December 2007) were collected in all postoperative women who had undergone major gynecological surgery (like abdominal hysterectomy, laparatomy, vaginal hysterectomy etc) and cesarean sections in obstetrics. Charts were reviewed and relevant clinical findings and bacteriological studies of catheter tip culture and sensitivity were noted. Results: There were total 390 major operations (both Gyne & Obs) during the study period. In obstetrics there were a total of 211 cesarean section. Files obtained were 186. Urine and catheter tip culture were obtained in 165 out of 186 cases. Positive culture was found in 76 out of 165 (46%). In gynecology, there were 179 major operations, out of which 130 files were obtained. Urine and catheter tip culture reports were available in 121 cases and 56 (46%) were found to be positive. In cesarean section, duration of catheterization was not associated with increased bacteriuria (p=0.926), while in gynecological surgery there was significant impact of catheterization duration on bacteriuria (p=0.042). In gynecological surgery, increasing patients’ age had important impact on bacteriuria (p=0.0004). Overall 46% had positive catheter tip culture. The most common organisms isolated were E coli, Enterococcus fecalis and Staph aureus. Conclusion: This study establishes that Foley catheter was associated with increased risk of bacteriuria in postoperative women following obstetrical and gynecological surgery. Key words: Bacteriuria, Foley catheterization, Catheter tip culture and sensitivity doi:10.3126/njog.v3i1.1437 NJOG 2008 May-June; 3(1): 35 - 38